Combined effect of purulent vaginal discharge and anovulation on pregnancy status in a large multi-state population of Holstein cows - P. Pinedo; J.E.P. Santos; K.N. Galvão; G.M. Schuenemann; R.C. Chebel; R.C. Bicalho; R.O. Gilbert; S.L. Rodriguez-Zas; C.M. Seabury; G.J.M. Rosa; W.W. Thatcher (JDS Communications, 2023)
The objective of this observational prospective cohort study was to evaluate the combined effect of purulent vaginal discharge (PVD) and anovulation (ANOV) on the reproductive performance of a large multi-state population of Holstein cows. Data were prospectively collected from 11,729 cows in 16 herds located in 4 regions in the United States [Northeast (4 herds), Midwest (6), Southeast (1), and Southwest (5)]. Cows were enrolled at calving and monitored weekly for disease occurrence, reproductive events, and survival. Prevalence of PVD was evaluated at 28 ± 3 d in milk and defined by the presence of mucopurulent to fetid vaginal discharge. Resumption of ovarian cyclicity was determined via transrectal ultrasonography at 40 ± 3 and 54 ± 3 d postpartum. Pregnancy diagnosis was performed by ultrasonography on d 32 ± 3 after artificial insemination (AI) and reconfirmed at d 60 ± 3 of gestation. Pregnancy loss (PL) was defined as a cow diagnosed pregnant at 32 ± 3 but nonpregnant at 60 ± 3 d after AI. The association of PVD and ANOV with pregnancy traits was analyzed using 4 PVD-cyclicity categories that considered the following combinations: NPVD-CYC = absence of PVD and cycling; PVD-CYC = presence of PVD and cycling; NPVD-ANOV = absence of PVD and anovular; and PVD-ANOV = presence of PVD and anovular. Multiple logistic regression and Cox proportional regression were used for the analysis of potential associations between PVD and cyclicity categories and pregnancy at first AI (PAI1), days from calving to pregnancy, and PL at first AI. The odds (95% confidence intervals) of pregnancy increased from cows in the PVD-ANOV category (reference category) to cows in NPVD-ANOV [2.09 (1.62–2.50)], PVD-CYC [2.52 (2.02–3.14)], and NPVD-CYC [3.46 (2.84–4.23)]. Similarly, days from calving to pregnancy were less for NPVD-CYC, followed by PVD-CYC, NPVD-ANOV, and PVD-ANOV (121.4, 137.2, 137.3, and 157.4 d, respectively). On the contrary, no clear association was identified between groups and PL. The results indicate that both PVD and ANOV had a negative impact on PAI1 and days from calving to pregnancy. The results indicated a variable magnitude in the negative impact on the reproductive traits analyzed when both conditions were combined.